2017
DOI: 10.1080/0142159x.2016.1254743
|View full text |Cite
|
Sign up to set email alerts
|

Peer review improves psychometric characteristics of multiple choice questions

Abstract: Peer-review practices of multiple-choice questions using guidelines can lead to improved psychometric characteristics of items; these findings have implications for faculty development programs in improving item quality, particularly for medical schools in early stages of transforming assessment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
2
15
0
3
Order By: Relevance
“…The importance of peer review processes in improving item quality has been established by numerous studies [34][35][36], and was found by our study to facilitate item writing through creating a sense of relatedness amongst writers. This is supported by findings from Lyness et al who suggested that an important measure in supporting relatedness amongst academics is to create structures that cultivate interpersonal relationships within this group [18].…”
Section: Discussionsupporting
confidence: 53%
“…The importance of peer review processes in improving item quality has been established by numerous studies [34][35][36], and was found by our study to facilitate item writing through creating a sense of relatedness amongst writers. This is supported by findings from Lyness et al who suggested that an important measure in supporting relatedness amongst academics is to create structures that cultivate interpersonal relationships within this group [18].…”
Section: Discussionsupporting
confidence: 53%
“…Allowing writers the autonomy to utilise training sessions at their own leisure thereby giving choices [21,23] could increase engagement and thus improve the effectiveness of these training measures. The importance of peer review processes in improving item quality has been established by numerous studies [38][39][40], and was found by our study to facilitate item writing through creating a sense of relatedness amongst writers. This is supported by findings from Lyness et al who suggested that an important measure in supporting relatedness amongst academics is to create structures that cultivate interpersonal relationships within this group [21].…”
Section: Practice Implicationssupporting
confidence: 53%
“…Another reason is because the purpose of the item will affect the magnitude of its discriminating power in relation to the total test. 3,6 The correlation of two indices was shown in Figure 1. Rank spearman correlation (r s ) was 0.37 with p-value 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed the benefit of implementing review process to improve MCQ quality, especially for new and emerging medical schools. 6 A study described an education center performed this process by conducting sessions to become peer-reviewers, to construct good MCQs and to give feedback of review process to the lecturers. The MCQ peer review practices based on the National Board of Medical Examination (NBME) guidelines can result in significant improvements in the quality of items that can eventually improve the validity of assessment scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation